MULHERES, DOCÊNCIA E CIÊNCIA: EPISÓDIOS DA CARREIRA CIENTÍFICA DE PROFESSORAS DA UNIVERSIDADE FEDERAL DE MATO GROSSO DO SUL - Zelia Vieira de Quevedo Bakargi (2023)
The theme of women in science brings to light women working as educators and researchers in academia, especially at the Federal University of Mato Grosso do Sul (UFMS), enabling a discussion about the intricacies of these trajectories, revealing their academic career, their socio- culture and its practices, since the need to highlight the specificities of women's trajectories in their scientific work is understood. Our thesis is that the stability transmitted by those responsible, in convergence with the valorization and encouragement of study practices and the attenuation of female gender socialization, are preponderant for women to be successful in their academic careers and position themselves in the field more assertively. To promote such discussion, the theoretical framework of this research uses Bourdieusian concepts, especially habitus, conceptualized as a unique system of dispositions for action, planned by each person in relation to the position they occupy in the social structure. To better understand the university as a field, we evoke the concept of scientific field, a structure in which agents occupy positions based on the accumulation of scientific capital and, to understand the resources that enable advancement in the field, the concept of capital was used, the which refers to the cultural, material or social advantages that individuals or families mobilize. The lack or insufficiency of this capital can subject the individual to symbolic violence, also a Bourdieusian concept, since, not being in possession of the culture of the dominant class, they suffer marginalization and discrimination. Our objective is to analyze which aspects of the experiences and practices of educators/scientists at the Federal University of Mato Grosso do Sul constituted in the primary, gender and school habitus ratify or break with the gender equality presupposed in the scientific field. To this end, a Bibliographical Review of scientific productions related to the topic and an analysis of the agents' experiences and practices regarding the gender perspective were carried out, aiming to verify whether these practices ratify the requirement for a male career model. The methodology used adopted qualitative research procedures, whose research instruments are directed towards the socio-historical-cultural delineation of the institution and the ways in which the mechanisms for maintaining this status quo were established, which aims to discourage the creation of “disparate” ways of producing science, as occurs with research under a gender bias. To this end, in parallel with the construction of the theoretical framework, a Bibliographic Review was carried out, and, after approval by the CEP, we carried out 8 (eight) interviews, with female professors, held at UFMS, and linked to a Postgraduate Program. After carrying out the research, with questions related to identification and family and school/academic life, later dealing with their understanding of what it means to be a woman, the analysis was carried out, in which the trajectories and mechanisms that the university has adopted were problematized. , or not, to achieve gender equality in this field as full of disputes as the scientific field, personified by UFMS. The analyzes indicate that the capital necessary for the development of this career is encouraged by family members/guardians, providing affective and emotional conditions and gender empowerment, in addition to the essential material infrastructure for its training, thus enabling the effectiveness and regularity of the practices necessary for the development of this career. development of cultural and social capital that gave them access, success and permanence in the scientific field.